Molecular genetic studies in a case series of isolated hypoaldosteronism due to biosynthesis defects or aldosterone resistance. (18th April 2018) - Turan, Ihsan; Kotan, Leman Damla; Tastan, Mehmet; Gurbuz, Fatih; Topaloglu, Ali Kemal; Yuksel, Bilgin
Summary: Background and Aim: Hypoaldosteronism is associated with either insufficient aldosterone production or aldosterone resistance (pseudohypoaldosteronism). Patients with aldosterone defects typically present with similar symptoms and findings, which include failure to thrive, vomiting, hyponatremia, hyperkalemia and metabolic acidosis. Accurate diagnosis of these clinical conditions therefore can be challenging. Molecular genetic analyses can help to greatly clarify this complexity. The aim of this study was to obtain an overview of the clinical and genetic characteristics of patients with aldosterone defects due to biosynthesis defects or aldosterone resistance. Design and Patients: We investigated the clinical and molecular genetic features of 8 consecutive patients with a clinical picture of aldosterone defects seen in our clinics during the period of May 2015 through October 2017. We screened CYP11B2 for aldosterone synthesis defects and NR3C2 and the three EnaC subunits ( SCNN1A, SCNN1B and SCNN1G ) for aldosterone resistance. Results: We found 4 novel and 2 previously reported mutations in the genes CYP11B2, NR3C2, SCNN1A and SCNN1G in 9 affected individuals from 7 unrelated families. Conclusion: Molecular genetic investigations can help confidently diagnose these conditions and clarify the pathogenicity of aldosterone defects. This study may expand the clinical and genetic correlations of defects in aldosterone synthesis or resistance.